2014
DOI: 10.1007/s13593-014-0252-3
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan antimicrobial and eliciting properties for pest control in agriculture: a review

Abstract: In agriculture, current control of pathogens relies mainly on chemical fertilizers and pesticides. However, alternative solutions are needed due to concerns for public health, environmental protection, and development of resistant pests. Chitosan is a nontoxic, biodegradable biopolymer showing antimicrobial and plant-immunity eliciting properties. Here, we review chitosan antimicrobial activities, modes of action, and the elicitation of plant defense responses. The major points are the following: (1) Chitosan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
206
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(216 citation statements)
references
References 164 publications
(185 reference statements)
2
206
0
8
Order By: Relevance
“…There have been several reports describing the use of chitosan for biotic and abiotic stress management in agriculture [73,[81][82][83][84][85]. Table 3 lists some of the applications of chitosan in crop production and protection.…”
Section: Chitosan In Crop Production and Protectionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several reports describing the use of chitosan for biotic and abiotic stress management in agriculture [73,[81][82][83][84][85]. Table 3 lists some of the applications of chitosan in crop production and protection.…”
Section: Chitosan In Crop Production and Protectionmentioning
confidence: 99%
“…Since the 1980s, the study of chitosan has been shift from a general sewage treatment agent to plant growth regulator, soil conditioner, vegetables and fruits antistaling agent, and seed coating agent, especially in the crop disease management. Several studies showed that chitosan is not only an antimicrobial agent but also an effective elicitor of plant systemic acquired resistance to pathogens [73,82,84,131]. This polymer has been reported to be the enhancer and regulator of plant growth, development and yield [85,132,133].…”
Section: Chitosan In Crop Production and Protectionmentioning
confidence: 99%
“…It is likely that the expression of genes related to basal defense of tomato was induced in plants supplied with Si and inoculated with bacteria. Another product of increasing use is chitosan, a nontoxic, biodegradable biopolymer with antimicrobial and plantimmunity eliciting properties (Xing et al 2014). Chitosan is applied against a range of plant pathogens including strains in the Pssc.…”
Section: Exclusion Elimination or Reduction Of Pathogen Inoculummentioning
confidence: 99%
“…Chitosan, the second most abundant polysaccharide, is known for its film-forming property, biodegradability, biocompatibility, antimicrobial property and importantly, for its mechanical properties, as they show similarity to medium chain commercial polymers (Xing et al, 2015). Recently, chitosan-based active packaging films incorporated with laponite immobilised silver nanoparticles have been developed for extending the storage life of litchi (Wu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%